Effectiveness of Causalitic Model Science Learning Device Integrated with Character Value and Local Wisdom to Improve Students' Problem-Solving Ability - Joni Rokhmat; Agus Abhi Purwoko; Aliefman Hakim; Huraiza Mahmudah; Syahrial A; Ni Nyoman Sri Putu Verawati; Galuh Elisa Roliana Fatimah; Lia Saptini Handriani (International Journal of Contextual Science Education, 2024)
This study aims to measure the effectiveness of science learning devices with causalitic model integrated character values and local wisdom to improve students' Problem-Solving Ability (PSA). The study used a mixed method as a modify of the explanatory design and statistical analysis using the Wilcoxon t-test. The analysis results show that the implementation of devices is significantly effective in developing the PSA of students of Public Junior High School (JHS) 3 Labuapi, West Lombok Regency, West Nusa Tenggara Province. The device developed has been proven to have the exact alignment for all learners when developing the PSA. The developed PSA includes six indicators, namely understanding (IPSA-1), selecting (IPSA-2), differentiating (IPSA-3), determining (IPSA-4), applying (IPSA-5), and identifying (IPSA-6). Statistical analysis was also performed on the difference in the final achievement of each indicator of PSA of the students of High-Group (Hi-group) and Low-Group (Lo-group) for each indicator of PSA (IPSA). The results show that the finals of IPSA-1 up to IPSA-4 have no difference for either Group, but for IPSA-5 and IPSA-6, there are significant differences. The average final PSA scores of the Hi-Group in the two indicators, respectively 77 and 75, are higher than those of the Lo-Group, 56 and 52.